KAZAKHSTAN AND NATO: EVALUATION OF COOPERATION PROSPECTS - SHAYMERGENOV, Timur; BIEKENOV, Marat (CENTRAL ASIA AND THE CAUCASUS, 2010)
For eighteen years now, relations between the Republic of Kazakhstan and the North Atlantic Treaty Organization have been steadily progressing and are characterized by positive dynamics. Kazakhstan views strategic partnership with NATO as an opportunity to integrate into the international security systems in order to reinforce national security by making use of the enormous military, technical, and economic potential that this organization and its members possess. In its cooperation with NATO, Kazakhstan is mainly looking to establish mutually advantageous and equal partnership that meets the republic’s present-day priorities in the military and defense sphere, in transforming and modernizing its armed forces, in counteracting the threats posed by terrorism and drug trafficking, in border security, science, and the environment.Bilateral Kazakhstan-NATO cooperation is characterized by developed institutional mechanisms of partnership and a broad contractual-legal cooperation base. Kazakhstan is rendering NATO comprehensive assistance in carrying out the peacekeeping operation in Afghanistan, and subdivisions of the Kazakhstan armed forces are also participating in the post-conflict restoration of Iraq. Joint operational-tactical military exercises are held every year. In addition, Kazakhstan’s official policy regarding the development of cooperation with the North Atlantic Alliance has always been consistent: membership in the Alliance is not an officially declared goal of Kazakh foreign policy. And, as domestic politicians point out, Kazakhstan does not have any plans to join NATO in the future.1 Nor does the republic have any intentions of deploying the Alliance countries’ military facilities or armed forces in its territory, as certain other countries of the region have done.On the other hand, since the collapse of the Soviet Union, NATO diplomacy has been keeping its sights on Kazakhstan, and the Organization is making insistent attempts to draw the republic into the orbit of Western influence by enlarging the format of partner programs. As we know, in the 1990s, NATO placed the main emphasis of its Central Asian strategy on partnership with Uzbekistan, but in so doing it did not downplay Kazakhstan’s role in any way. The thing is that Western strategists have always regarded Uzbekistan as an important element in the regional dimension, while Kazakhstan plays a principal role in implementing the Eurasian strategy as a whole.2